Nepoznavanje kulturnih razlik kot ovira mednarodnega poslovanja slovenskih podjetij? - Kralj, Tina (Teorija in praksa, 2017)
This article contributes new knowledge about the extent to which Slovenian managers recognise the meaning and importance of cultural differences and skills in multicultural communication when working with foreign business partners, how they acquire new knowledge in this field and explores whether they are familiar with the cultural characteristics of different European and non-European countries. It concludes that the deficiency in such knowledge poses a barrier to successful cooperation. However, the respondents to a survey we conducted were aware of the importance of cross-cultural competencies and how expensive mistakes caused by the lack of such knowledge can be. Our own empirical evaluation is based on surveys conducted among businessmen and students. In order to improve cross-cultural competencies, greater multicultural training is needed at both universities and within companies.
Keywords: Intercultural communication; Intercultural relations; International business; Medkulturni odnosi; Medkulturno komuniciranje; Mednarodno poslovanje; podjetja; Slovenia; Slovenija